A comparison of sutureless flanged fixation and 4-point Gore-Tex fixation for scleral-fixated intraocular lenses: a pilot study - Raina, Usha K.; Kumar, Brajesh; Bhattacharya, Shruti; Saini, Varun; Kumar Gupta, Shantanu; Goyal, Jawaharlal (Digital Journal of Ophthalmology, 2022)
Purpose Scleral-fixation of intraocular lenses (IOLs) provides an option for eyes that lack sufficient capsular support for in-the-bag IOL placement. The latest techniques for lens fixation include use of a novel suture material, Gore-Tex, and a sutureless method, with flanged intrascleral fixation. The purpose of this pilot study was to compare these methods in terms of anatomic and clinical outcomes. Methods A total of 35 eyes of patients 18-60 years of age who presented with aphakia, subluxated lens, or ectopia lentis were randomized into two groups. Group A (15 eyes) underwent flanged intrascleral IOL fixation using the Yamane technique; group B (20 eyes) underwent 4-point transscleral fixation of IOL using Gore-Tex suture. The following parameters were compared between groups on day 1, week 3, and month 6 postoperatively: logMAR uncorrected and best-corrected visual acuity, retinoscopy, IOL centration on slit-lamp biomicroscopy, and IOL tilt on ultrasound biomicroscopy. Results Postoperative visual acuity was better in group B: uncorrected, logMAR 0.89 ± 0.22 versus 0.72 ± 0.24 (P = 0.046); best-corrected, logMAR 0.51 ± 0.18 versus 0.37 ± 0.26 (P = 0.016). No significant difference was found in postoperative retinoscopy and astigmatism between groups. IOL tilt (>100 µm) occurred in 8 cases in group A and in 9 cases in group B; 87% in group A and 100% in group B were well centered. Complications in both groups were minimal. Conclusions In our small study cohort, both sutureless flanged IOL fixation and Gore-Tex sutured scleral IOL fixation resulted in excellent visual rehabilitation of patients with aphakia and subluxated lenses. Patients who underwent Gore-Tex suture fixation experienced better postoperative visual acuity, IOL centration, and stability.